2023
DOI: 10.1111/jasp.12959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fact‐checking warning labels and social endorsement cues on climate change fake news credibility and engagement on social media

Abstract: Supplementary materials for this manuscript, including code, figures, and results, are available in the project's repository on the Open Science Framework (OSF): https://osf.io/ugt2v/ Acknowledgments: We thank Carina Kemmer and Susanne Grundler for their substantial support in the early stage of this project, particularly in conceptualization and data collection. We thank Regina Rockinger for her support with literature research. We thank David Goretzko and Florian Pargent for their statistical advice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…If the source is credible, meaning that it has a proven track record of providing accurate and unbiased information, the news story is more likely to be credible. On the other hand, if the source is unreliable or has a history of publishing inaccurate or biased information, the news story may be less credible or even misleading [52]. In the digital age, where anyone can publish news or information online, it is important to be critical of sources and to verify information before accepting it as true.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the source is credible, meaning that it has a proven track record of providing accurate and unbiased information, the news story is more likely to be credible. On the other hand, if the source is unreliable or has a history of publishing inaccurate or biased information, the news story may be less credible or even misleading [52]. In the digital age, where anyone can publish news or information online, it is important to be critical of sources and to verify information before accepting it as true.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially important in the context of social media, where news stories can spread quickly and without any fact-checking or editorial oversight. By paying attention to the source of a digital news story, readers can better assess its credibility and make informed decisions about whether or not to believe it [50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…Although these studies provide some evidence that endorsement information may influence belief in false information, other studies have found no effect of perceived endorsement on (mis)information belief (Koch et al, 2023;Mena et al, 2020). Further, almost all studies have exclusively focused on positive engagement (i.e., likes and shares), neglecting how negative engagement (which may be perceived as disendorsement; e.g., dislikes) might impact belief.…”
Section: Introductionmentioning
confidence: 82%
“…The sentences are extracted from the web server, and a deep learning system keeps track of the assertions made. Therefore, using manual and automatic fact-checking, our strategy used fact-checking to identify and match propaganda news claims [63]. As input documents, the architectural pipeline transforms the news from the source file.…”
Section: Protext Labeling and Matching Claimsmentioning
confidence: 99%